Using the galectin-3 test to predict mortality in heart failure patients: a systematic review and meta-analysis - Chen, Yueh-Sheng; Gi, Weng-Tein; Liao, Tin-Yun; Lee, Meng-Tse Gabriel; Lee, Si-Huei; Hsu, Wan-Ting; Chang, Shy-Shin; Lee, Chien-Chang (Biomarkers in medicine, 2016)
Aim: Galectin-3 (Gal-3) is a new biomarker for assessing prognosis of heart failure (HF) patients. This systemic review and meta-analysis aims to examine Gal-3’s ability in assessing prognosis of HF patients. Method: We searched MEDLINE and Embase up to November 2014. Test performance characteristics were summarized using forest plots and hierarchical summary receiver operating characteristic curves. Results: The diagnostic odds ratio of Gal-3 in predicting mortality in chronic HF patients was 2.36 (95% CI: 1.71-3.26) and 2.30 (95% CI: 1.76-3.01) in acute HF patients. Conclusion: Elevated levels of Gal-3 are associated with mortality in both acute and chronic HF patients. However, current evidence does not support sole use of Gal-3 for prognosis evaluation of HF patients.
Gesehen am 30.04.2020